Economic growth & development: a mathematical introduction - Neher, Philip A. (New York : Wiley, 1971)
This book is primarily on intermediate micro economic theory. It further explains some of the mathematical methods using the familiarize graphic techniques.
Includes bibliographies and index
ucj 17/01/2019
Loans
Keywords: Economic development